Отходы производства перманганата калия и возможности их утилизации - Уберман, В. И.; Александров, А. Н.; Васьковец, Людмила Антоновна (НТУ "ХПИ", 2009)
100 thousand tons of sludge from potassium permanganate production in Saki chemical plant (Crimea AR) more than 25 years is disposed on temporary site in immediate proximity to Sasyk–Sivash lake. The problem of the sludge utilizing as fertilizers and for chemical reclamation of soils is considered. Industrial origin, contemporary components and properties of the sludge is studied. It is founded the sludge is inorganic substance poorly soluble in water, it includes many of heavy metals (HМ), from which Mn, Ni, Sr is limiting ones, and it is characterized as IV class of danger. Environmental criteria to find the possibility for direct inclusion the sludge into agricultural soils such as HM content and risk of overdosing is proposed based on modern EC and Ukrainian claims. It is established the sludge without previous additional treatment do not be directly included into a soil. It is assessed high (17–18%) risk of overdosing for the direct inclusion method proposed in previous researches
Keywords: шлам; производственные источники шламов; агрохимия; шламохранилище